Soil change induced by the application of biodigested vinasse concentrate, and its effects on growth of sugarcane - Silva, Juliana [UNESP]; Cazetta, Jairo [UNESP]; Togoro, Aluisio [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
Vinasse (or stillage) is a byproduct from ethanol production, which contains organic matter, K, N, and other plant nutrients that is regularly used as soil fertilizer. However, high transportation costs limits its application in areas far from distilleries. The possibility of biogas production from vinasse, and the direct or indirect advantages of its use, is a way to reduce costs due to its concentration. Biodigested vinasse concentrate (BVC) is an alkaline product that is very different from common vinasse. Therefore, the objective of this study was to compare the effect of BVC with common vinasse (CV) or KCl, with or without N fertilization, on soil fertility and growth and nutrition of sugarcane (Saccharum officinarum L.) plants. Plants were grown in pots containing Oxisol under different treatments and maintained for 60 d under greenhouse conditions; variables related to soil fertility, plant growth, and mineral nutrition were evaluated. It was observed that adding BVC induces higher soil pH (5.9 to 6.3) and lower potential acidity (13 to 10 mmolc dm-3) compared with KCl, and similar soil chemical changes to CV addition. Plants fertilized with BVC and N showed lower root dry matter (DM) (4.02 g) compared with those fertilized with KCl and CV (6.3 and 5.44 g, respectively). Plants fertilized with BVC have similar total DM (18.25 and 20.31 g) accumulation and nutritional conditions compared with those fertilized with CV and KCl. Plants fertilized with BVC had the highest Na accumulation (0.36 and 0.48 g plant-1).
Keywords: Biodigestion; Plant growth; Saccharum spp; Soil fertility; Stillage